COMPARATIVE PHYSIOLOGICAL RESPONSE OF SAINFOIN (ONOBRYCHIS VICIAEFOLIA) SEEDLINGS TO ALKALINE AND SALINE-ALKALINE STRESS - G.-Q. Wu1; H. Li; Y.-H. Zhu; S.-J. Li (Journal of Animal and Plant Sciences, 2020)
Salt-alkali stress is a major environmental factor that seriously limits crops development and productivity worldwide. The objective of this study is to compare growth and physiological responses of sainfoin (Onobrychis viciaefolia) to alkali (NaHCO3) and salt-alkali (NaCl: NaHCO3) stress, by investigating biomass, photosynthetic pigments, antioxidant enzymes, inorganic ions, organic substances such as proline and sugars. It was shown that both alkaline and saline-alkaline stress treatments significantly reduced fresh weight (FW) and dry weight (DW), chlorophyll (Chl) contents, K+ concentrations, antioxidant enzymes activity and soluble sugars contents, whereas clearly increased malondialdehyde (MDA), proline and Na+ concentrations in sainfoin plants compared with control (no added NaCl and NaHCO3). It is also observed that in the 150 mM NaHCO3, peroxidase (POD) activity, soluble sugar contents and K+/Na+ ratio in plants under NaHCO3 treatment were lower than those in plants under NaCl: NaHCO3 treatment. These results suggested that the damages caused by alkaline stress on the growth of sainfoin plants are more serious than those caused by saline-alkaline stress treatments. The findings of the present work provide a basis for understanding the physiological responses to saline-alkaline stress in forage legumes.
Keywords: Forage legume; antioxidant enzymes; proline; soluble sugars; malondialdehyde